Penerapan Metode Vikor Pada Pengambilan Keputusan Seleksi Calon Penerima Beasiswa Baznas Iain Padangsidimpuan - An'nisaa, Kiky (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This decision is something that is very influential in the process of facing the chosen alternative, as well as the decision to select the acceptance of scholarships at IAIN Padangsidimpuan. To get the scholarship, it must be in accordance with the rules that have been set. The criteria set in this case study are activeness in organizations on and off campus, achievements and Grade Point Average (IP) and Cumulative Grade Point Average (GPA). To avoid the subjectivity of the resulting decision, a decision support system is needed that can help assess students in deciding scholarship recipients. One way to process the determination of students for scholarship recipients is with the decision support system Vise Kriterijumska Optimizajica I Kompromisno Resenje (VIKOR) method. Decision Support Systems are information systems that provide information, decision-making systems in semi-structured situations and unstructured situations where no one knows exactly how decisions should be made. There are several methods that can be used in a Decision Support System (SPK), including the WP method, WASPAS, MOORA, TOPSIS, ELECTR, PROMETHEE, AHP, VIKOR. The results showed that the Decision Support System for Selection of Exemplary Health Worker Candidates by Applying the WASPAS Method can be done quickly, precisely, and objectively.